Correlation development and parametric investigation for thermal–hydraulic characteristics of flying-wing fin. (25th January 2023) - Wang, Ying; Lin, Zibo; Lei, Xiangshu; Li, Xinyang; Liu, Shiqun; Liu, Yingwen
Highlights: The thermal–hydraulic performance of the flying-wing fin is investigated. The correlations with flying-wing fin are proposed by response surface method. The effects between different structural parameters are investigated in detail. Better performance is obtained by optimizing geometric parameters. Abstract: The present study investigates thermal–hydraulic characteristics and structural parameters of the flying-wing fins. 165 cases based on the response surface method (RSM), considering 6 geometric parameters, are carried out. Firstly, the correlations of the flying-wing fin's heat transfer ( j -factor) and flow friction ( f -factor) are proposed using numerical simulations. The maximum deviations of the correlation with j -factor and f -factor are 8.53 % and 9.51 %, respectively. Secondly, the effects of geometric parameters are investigated respectively using the RSM model in detail at Re of 3000. The j -factor and f -factor are positively correlated with fin pitch ( Fp ) and amplitude ( A ) while negatively correlated with wavelength ( L ) and fin height ( Fh ). The j -factor and f -factor rise and subsequently drop as the inclined angle ( θ ) increases. Evaluating the thermal performance shows that the optimum θ is 80°. The f -factor has a turning point at the angle of 75°. Regarding the effects between parameters, the lower f -factor can be obtained at large Fp when the fin is short while at small Fp when the fin is tall. The A and Fh change the trend of θ on j -factor and f -factor. Eventually, optimized geometrical parameters of the flying-wing fin are obtained by the desirability approach at Re  = 3000.